Legal Protection Against Human Trafficking: A Dilemma in Indonesia and the ASEAN Region - Tampubolon, Theresia; Tan, Winsherly; Ninne Zahara Silviani (Universitas Internasional Batam, 2025)
Human trafficking remains a major humanitarian crime problem worldwide. Indonesia has made efforts to combat human trafficking by establishing various regulations that serve as the main foundation in this fight, one of which is Law No. 21 of 2007. The framers of the law used the Palermo Protocol as the foundation for its creation. As a transnational crime, human trafficking has also prompted ASEAN, as a regional organization, to take a stand. Since the 1990s, ASEAN has included human trafficking in its agenda to be collectively eradicated. However, human trafficking practices in Indonesia and ASEAN continue to increase, with various methods of operation. Unfortunately, the majority of the victims of this crime are women and children. This article aims to examine the formalization of national law and ASEAN's role at the regional level in combating human trafficking within the framework of international law. This research employs a normative legal approach. The findings indicate a disconnection between national regulations and the fundamental norms upon which they were based, as well as disharmony with other national regulations. Meanwhile, in the ASEAN context, the formation of hard law has not yet been fully implemented, a situation further compounded by the rigid principle of non-intervention in ASEAN.